EKSISTENSI MANUSIA DAN TUGAS POKOKNYA DALAM TINJAUAN PENDIDIKAN ISLAM - Andi Abdul Hamzah (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2015)
This article describes the problem of human existence and the main task in the review of Islamic education. From the discussion, it is understood that that man as a creature of God Almighty. must be able to carry out the mandate of Allah. , the duties of life on earth. Human beings Allah. has two main tasks, namely: (1) as' abdullah , the servant of Allah. to be submissive and obedient to all the rules and His will and serve Him only; and (2) as the caliph of Allah swt. on earth, which includes the implementation of the tasks of the Caliphate of self, family, society, and the nature of the task Caliphate. It was hinted on the need for a balanced attitude in life, which is balanced between the needs of the material with the spiritual or Ruhiyah. This means the need for implanted Sufi soul coupled with the practice of Islamic law, particularly worship, remembrance, contemplation, muhasabah and so on.